Trade and growth in the Philippines; an open dual economy - Hicks, George L.; McNicoll, Geoffrey (Ithaca: Cornell University Press, 1971)
This study of the postwar Philippe economy in the analytical framework of open dualism was originally prepared as part of the Philippine project of the Centre for Development Planning, National planning Association, Washington, under a contract with the Agency for International Development.
Includes index
Bibliography: p. 232-240.
usc 25/01/2019
Loans
Keywords: Dual economy; Commerce; Economic history; Philippines